UPAYA MENINGKATKAN KEMAMPUAN OPERASI HITUNG PECAHAN MENGGUNAKAN MODEL PEMBELAJAAN DIRECT LEARNING PADA SISWA KELAS V SDN SUKASARI 2 - Retnaningtyas, Dian; Suparman, Tarpan; Fitri, Ayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of the research is to analyze the increase in mathematical skills in fraction calculation operation material for class V students at Sukasari 2 National Elementary School using the direct learning method, because of the importance of problem solving skills in mathematics education. The research method used is a descriptive qualitative method. Determining the subjects of this research used a purposive sample. This research provides a detailed analysis of each student's performance on the problem-solving ability test and interviews are also conducted with students to validate the research results. From the results of the fraction calculation operation ability test of 25 students in class V of Sukasari 2 Elementary School, it was found that 44% of students had results in the "High" group, 16% of students had results in the "medium" group, 40% of students had results in the "Low" group.